Estimation of reaction kinetics of geopolymers at early ages. (March 2020) - Hu, Zhangli; Wyrzykowski, Mateusz; Lura, Pietro
Abstract: The degree of reaction and the reaction kinetics of the reactants in geopolymers correlate closely to their mechanical properties and their durability. However, quantifying the reaction using conventional methods is challenging, especially for alkali activated siliceous fly ash with low reactivity. In the present study, a novel method to estimate the reaction kinetics of geopolymers at early ages based on the evolution of the internal relative humidity is proposed. The experimental results show increasing internal relative humidity of the two studied fly-ash based geopolymers with increasing hydration time. The internal relative humidity increases due to the reduction of the ion concentration in the pore solution as they become consumed during the reaction of the fly ash. Verified by comparison with compressive strength, heat release in isothermal calorimetry and degree of reaction measured with selective dissolution, this new method is useful to estimate the reaction kinetics of geopolymers having limited self-desiccation.